Clinical indicators of midface fracture in patients with trauma. Issue 4 (16th October 2012) - Smith, Hayden L.; Chrischilles, Elizabeth; Janus, Todd J.; Sidwell, Richard A.; Ramirez, Marizen; Peek‐Asa, Corinne; Sahr, Sheryl M.
Abstract: Background/Aim: Midface fractures are commonly present and difficult to diagnose in trauma patients. The objective of this study was to determine clinically accessible indicators of midface fracture. Material and Methods: A case‐control study design was used to determine clinical indicators of midface fracture. Population source was a level I trauma center registry for years 2007–2009. Cases had a documented midface fracture. Patient and trauma characteristics were compared between cases and controls. Multivariate logistic regression analysis determined significant indicators of midface fracture. Results: Study sample included 83 cases and 83 frequency‐matched controls. Cases had a total of 211 fractures with a median of two midface fractures per person. Common fractures were orbital (41%), malar and maxillary (28%), and nasal bones (19%). Patients with midface fracture were significantly different than patients without midface fracture in severity of injury and were more likely to have a traumatic brain injury. Significant clinical indicators of fracture were maxillary sinus opacification, ethmoid sinus opacification, forehead laceration, periorbital contusion, epistaxis, and injury mechanism ( P  < 0.05). Patients with midface fracture had a 63 times greater odds for maxillary sinus opacification. The multivariable model correctly classified the presence and absence of midface fracture in 95% of study sample. Conclusions: Determined indicators of midface fracture provided a high level of discrimination in fracture status. Indicators can be used by clinicians to help detect possible midface fractures. Future prospective research on midface fracture indicators can assist in establishing their generalizability and impact on fracture detection, care, and outcomes.